Research on Characteristics of Audio DAC Sigma-Delta Modulator on Field Programmable Gate Array - Puidokas, V.; Marcinkevičius, A. J. (Elektronika ir Elektrotechnika, 2008)
The original architectural scheme of a designed audio Sigma Delta DAC on the FPGA whose application in a computer sound system allows refusing of an analogue sound track and improving the sound quality is presented. Modelling results of the audio interpolator filters transmission characteristics and the Sigma Delta modulator’s quantization noise parameters are given. It was determined that requirements are met best by a CIC filter amplitude frequency characteristics when the interpolation multiplier is L=8, the number of stages is N = 6, the input string length is 16 bits, the output string length is 31 bits, and the discretization frequency is 2.8224 MHz. The results of the modulator modelling showed that when a sound signal frequency band is of 20 kHz the modulator’s effective number of bits is 16, while the quantization noise power is minus 118dB. The modelling results are also proven by the experimental research when a DAC has been realized with Xilinx Spartan XC3S400-4PQ208 on the array. Ill. 12, bibl. 4 (in English; summaries in English, Russian and Lithuanian).